The nanosilica hazard: another variable entity - Napierska, Dorota; Thomassen, Leen CJ; Lison, Dominique; Martens, Johan A; Hoet, Peter H (Particle and fibre toxicology, 2010)
Silica nanoparticles (SNPs) are produced on an industrial scale and are an addition to a growing number of commercial products. SNPs also have great potential for a variety of diagnostic and therapeutic applications in medicine. Contrary to the well-studied crystalline micron-sized silica, relatively little information exists on the toxicity of its amorphous and nano-size forms. Because nanoparticles possess novel properties, kinetics and unusual bioactivity, their potential biological effects may differ greatly from those of micron-size bulk materials. In this review, we summarize the physico-chemical properties of the different nano-sized silica materials that can affect their interaction with biological systems, with a specific emphasis on inhalation exposure. We discuss recent in vitro and in vivo investigations into the toxicity of nanosilica, both crystalline and amorphous. Most of the in vitro studies of SNPs report results of cellular uptake, size- and dose-dependent cytotoxicity, increased reactive oxygen species levels and pro-inflammatory stimulation. Evidence from a limited number of in vivo studies demonstrates largely reversible lung inflammation, granuloma formation and focal emphysema, with no progressive lung fibrosis. Clearly, more research with standardized materials is needed to enable comparison of experimental data for the different forms of nanosilicas and to establish which physico-chemical properties are responsible for the observed toxicity of SNPs.